Analisis Biaya Kualitas Lingkungan PT PIP Karawang - Imam Nurudin; Yanti Yanti; Rohma Septiawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study is to provide an overview and new insights into the application of environmental quality costs in manufacturing companies, especially PT PIP Karawang. This type of research is qualitative with a case study approach and uses qualitative descriptive analysis techniques. This research reveals that PT PIP has not classified environmental costs as formulated by Hansen and Mowen. PT PIP Karawang has incurred costs related to environmental quality but the classification is still mixed with other costs related to production activities. Regarding the analysis of environmental quality costs according to PSAK, PT PIP has issued costs related to its environmental activities. However, these costs have not been specifically identified by the company, because the identification carried out by PT PIP in carrying out the stages of environmental cost treatment is treated as factory overhead costs. In addition, there is no recognition and measurement of environmental costs incurred according to PSAK, so PT PIP applies the recognition and measurement of environmental costs in accordance with Company policy. PT PIP Karawang has not reported and disclosed the environmental costs incurred because the disclosure of environmental costs is disclosed as overhead costs, so there is no need for special presentation in the financial statements. In addition, PT PIP Karawang has disclosed the GRI 306 standard regarding disclosure of wastewater (influent) and waste management which consists of reporting the volume of waste, type of waste, transportation of waste in collaboration with a transportation company or a utilization company that already has a license from the Ministry of Environment (KLH). Keywords: Environmental Quality Cost, Hansen & Mowen, PSAK, GRI 306